The Influence of the Course Review Horay Type Model on Social Studies Learning Outcomes in the Struggle Material of the Heroes in Grade IV - Nera Nera; Diana Pramesti; Erika Fitri Wardani (JURNAL PENDIDIKAN IPS, 2023)
This research is motivated by the problem that teachers have not applied the right model in the learning process and there is a tendency to understand that social studies are considered as a lesson that tends to be memorized. The purpose of this study was to determine the effect of the Course Review Horay Type Learning Model on Social Studies Learning Outcomes in the material Struggle of the heroes of class IV SD Negeri 4 Air Gegas. This study uses quantitative research with the Quasi-Experimental Design method with Nonequivalent Control Group Design. The sampling technique in this study used saturated sampling. The sample of this research was 23 students of class IV A and 23 students of class IV B. The data collection technique used was a test. The data analysis technique used is the normality test, homogeneity test along with hypothesis testing using the t-test sample-related polled variant. This result is shown in the calculation of count = 4.820 > stable = 2.074, this shows that Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the Course Review Horay type learning model on social studies learning outcomes in the Struggle of Heroes Class IV SD Negeri 4 Air Gegas material. This is because the learning process that is carried out using the Course Review Horay model makes students more active and interested in participating in the learning process in class so that students better understand the material presented.